Lipid accumulation in macrophages confers protumorigenic polarization and immunity in gastric cancer. Issue 11 (18th September 2020) - Luo, Qin; Zheng, Naisheng; Jiang, Li; Wang, Tingting; Zhang, Peng; Liu, Yi; Zheng, Peiming; Wang, Weiwei; Xie, Guohua; Chen, Lei; Li, Dongdong; Dong, Ping; et al.
Abstract: Heterotypic interactions between tumor cells and macrophages can enable tumor progression and hold potential for the development of therapeutic interventions. However, the communication between tumors and macrophages and its mechanism are poorly understood. Here, we find that tumor‐associated macrophages (TAM) from tumor‐bearing mice have high amounts of lipid as compared to macrophages from tumor‐free mice. TAM also present high lipid content in clinical human gastric cancer patients. Functionally, TAM with high lipid levels are characterized by polarized M2‐like profiling, and exhibit decreased phagocytic potency and upregulated programmed death ligand 1 (PD‐L1) expression, blocking anti–tumor T cell responses to support their immunosuppressive function. Mechanistically, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identifies the specific PI3K pathway enriched within lipid‐laid TAM. Lipid accumulation in TAM is mainly caused by increased uptake of extracellular lipids from tumor cells, which leads to the upregulated expression of gamma isoform of phosphoinositide 3‐kinase (PI3K‐γ) polarizing TAM to M2‐like profiling. Correspondingly, a preclinical gastric cancer model is used to show pharmacological targeting of PI3K‐γ in high‐lipid TAM with a selective inhibitor, IPI549. IPI549 restores the functional activity of macrophages and substantially enhances the phagocytosis activity and promotes cytotoxic‐T‐cell‐mediated tumor regression. Collectively, this symbiotic tumor‐macrophage interplay provides a potential therapeutic target for gastric cancer patients through targeting PI3K‐γ in lipid‐laden TAM. Abstract : TAM with high lipid levels were characterized by M2‐like polarized profiling. Lipid accumulation in TAM was caused by increased uptake of extracellular lipids from tumor cells. Pharmacological targeting of PI3Kγ in high‐lipid TAM with a selective inhibitor, like IPI549, restores the functional activity of TAM and substantially enhances anti–tumor immunity activity in vitro and in vivo.